Protease production by Serratia liquefaciens NRC1 using fish gut waste as a sustainable approach to antimicrobial peptide generation and combating Candida auris acquired resistance - Shaymaa A. Ismail; Heba M. Shalaby; Amira A. Hassan; Marwa Mahmoud; Bahgat Fayed (Microbial Cell Factories)
Abstract Background The global rise of antimicrobial resistance has accelerated the search for sustainable and eco-friendly therapeutic alternatives. This study evaluates fish gut waste (FGW) as a low-cost, renewable substrate for producing antifungal peptides through the proteolytic activity of Serratia liquefaciens NRC1. Result Optimization of protease production using statistical designs resulted in a fourfold increase in enzyme yield. The protease demonstrated stability at neutral pH and moderate temperatures (40–50 °C), and efficiently hydrolyzed complex proteins such as collagen and keratin. Peptides generated from FGW hydrolysis exhibited significant antifungal activity against Candida auris (C. auris), with a MIC₅₀ of 5.1 ± 0.08 mg/ml. Unlike fluconazole, repeated peptide exposure did not induce resistance, nor did it alter the expression levels of key resistance genes (CDR1, ERG11), as confirmed by qRT-PCR. Peptide profiling using MALDI-TOF/MS, coupled with in silico analysis via AMPfun, identified multiple candidates with predicted antifungal properties. Conclusion This research highlights the potential of fish gut waste-derived peptides as a sustainable and effective antifungal strategy against C. auris, offering an alternative to conventional antifungal drugs.